Physical and psychosocial comorbidities of pediatric hidradenitis suppurativa: A retrospective analysis. Issue 5 (31st August 2021) - Seivright, Justine R.; Collier, Erin; Grogan, Tristan; Hogeling, Marcia; Shi, Vivian Y.; Hsiao, Jennifer L.
Abstract: Background/Objectives: Hidradenitis suppurativa (HS) is understudied in the pediatric population. Adult HS patients are known to have a high comorbidity burden. We aimed to describe physical and psychosocial comorbidities in a cohort of pediatric HS patients. Methods: A retrospective chart review of pediatric HS patients at a single academic institution was conducted. Data on patient demographics, disease characteristics, and physical and psychosocial comorbidities in pediatric patients with HS were collected and analyzed. Results: Seventy‐three pediatric patients were included in this study, 81% female. Mean (SD) age of HS disease onset was 12.6 (2.9) years. Comorbid conditions were reported in 68 of 73 (93%) patients. Significantly increased rates of several comorbidities were seen in our cohort as compared to the general US pediatric population. Metabolic and endocrine abnormalities were prevalent, with 52% (22/42) patients with obesity and 10% (6/59) with polycystic ovary syndrome. The most common cutaneous comorbidity was acne vulgaris, seen in 37% (27/73) of patients. Over one quarter (21/73, 29%) of patients had either an anxiety or depression disorder. Almost one‐fifth (14/73, 19%) of our cohort had a diagnosis of asthma and other reactive airway diseases. Only one‐third (24/73, 33%) of patients had documentation regarding impact of HS on their daily life. Overall, comorbidities largely did not significantly differ based on race, gender, or disease severity. Conclusions: Pediatric patients with HS face a high‐comorbidity burden, especially with psychiatric conditions. Early identification, including routine mental health screening, and management of comorbidities is warranted in the pediatric HS population.